Protein oxidation during temperature-induced amyloid aggregation of beta-lactoglobulin. (15th August 2019) - Keppler, Julia K.; Heyn, Timon R.; Meissner, Philipp M.; Schrader, Katrin; Schwarz, Karin
Highlights: Amyloid aggregates at pH 2 and pH 3.5 differed in their building blocks. All aggregate building blocks changed towards smaller peptides after >48 h incubation. Apparent dityrosine oxidation reached a maximum after 5 h incubation. Protein carbonyls were not significantly increased during the first 5 h of fibril preparation. The amyloid aggregates were deteriorated after 72 h incubation. Abstract: Although the connection between protein oxidation, amyloid aggregation and diseases such as Alzheimer's is well known there is no information on such effects during preparation of beta-lactoglobulin fibrils. Different morphologies of amyloid aggregates of beta-lactoglobulin were prepared by incubation at pH 2 or pH 3.5 for up to 72 h. After 5 h, amyloid aggregates at pH 2 formed typical fibrils, which consisted of peptides. At pH 3.5, the amyloid aggregates were worm-like and consisted of intact protein. After 72 h, the building blocks at both pH values changed towards smaller peptides. The apparent tyrosine oxidation reached a maximum after 5 h at both pH values, whereas N- formylkynurenine and carbonyls increased continuously during 72 h. In case amyloid structures are used as edible material, the health related effects caused by protein oxidation needs to be considered.